Poética do fracasso: dramaturgia e encenação no teatro de Samuel Beckett - Santos, Felipe Augusto de Souza (2015)
This research aims to investigate issues of theatrical aesthetics and the process of creation of Samuel Beckett, from a study on aspects of his work as a playwright and director of his own plays. First it will be made an approach about the relationship between text and scene in Beckett s work, that is, we will make a survey of the major aesthetic and structural features of plays such as Waiting for Godot, Endgame, Happy days and Footfalls, in order to problematize some of major issues involving the dramaturgy of Beckett, and also a study of the trajectory of Beckett from playwright to director. Later, we will make an analysis of the dramaturgical text of Krapp s last tape, using concepts from the writings of Mikhail Bakhtin and the Circle, such as dialogism, polyphony and chronotope, and also a reflection on the various performances of Krapp s last tape directed by Beckett. For this, we will use an unpublished translation of Krapp s last tape held by the researcher and published in this work as well as Beckett s directing notebook, with notes of the staging process of his version of Krapp s last tape performed at the Schiller-Theater in Berlin in 1969, and the changes undergone by the dramatic text. The results suggest the importance of the staging process performed by Beckett on some of his major plays, particularly Krapp s last tape, as a revising and defining element of his dramaturgy